Evaluation of Prescribing Indicators in a Paediatric Population Seen in an Outpatient Consultation at the Gaspard Kamara Health Centre in 2019 (Senegal) - Oumar Bassoum; Mouhamadou Faly Ba; Ndèye Marème Sougou; Djibril Fall; Adama Faye (MDPI AG, 2021)
Introduction: Data on drug use in paediatrics are scarce in Senegal. The objective of this study was to assess the prescribing indicators in a paediatric population seen in an outpatient consultation at a Health Centre in Dakar, Senegal. Methods: A retrospective and analytical study was conducted. The study population consisted of prescriptions for children aged 0 to 14 years who were seen in ambulatory consultation between 1 June and 30 November 2019. The sample size was 600 prescriptions. The systematic survey was then conducted. Five prescription indicators recommended by the World Health Organization were calculated. The R software was used for descriptive analysis, bivariate analysis and binomial logistic regression. Results: The average number of drugs per prescription was 2.56. The proportion of drugs prescribed under the International Nonproprietary Name (INN) was 18.9%, while the proportion of drugs on the National Essential Medicines List (NEML) was 41.3%. The proportions of prescriptions with at least one antibiotic and one injectable product were 41.5% and 1.3%, respectively. Conclusions: This study showed that prescribing habits were inadequate. Thus, it would be necessary to move towards continuing training of prescribers in the wise use of medicines.